‘Work tomorrow?’: the lived experiences of temporary agency workers in a UK fresh food factory - Carter, Peter James (2022)
This study examines the lived experiences of temporary agency workers in a UK fresh food factory. The UK food supply chain, like other lower paid and lower skilled sectors, is heavily reliant on this precarious form of employment and the voice of these workers has not been adequately heard. Whilst temporary agency work has been subject to extensive research, few accounts take into consideration the view from below to consider the overall lived experiences of these workers. This is surprising and, given the significance of this form of employment, warrants further examination. In this study I give an ethnographic account of the lived experiences of temporary agency workers in a salad processing factory, focusing on three aspects. The first aspect considers precarious work and employment insecurity and explores the experiences of temporary agency workers as they seek work and then aim to maintain work, whilst the second aspect examines these agency workers as they undertake work. These temporary agency workers experience multi-faceted relationships whilst at work - which is the third aspect of their lived experiences that this study examines. The ethnographic approach that I adopted for this study combined participant observations and semi structured interviews to provide valuable insights into the work experiences of temporary agency workers. As the motivation for this study was to further understand the lived experiences of temporary agency workers in the food supply chain, an ethnographic approach was necessary as we cannot really learn a great deal about what actually happens or about how things work in organizations without undertaking the intensive and close-up participative research that is central to an ethnographic approach. By examining the lived experiences of temporary agency workers in this way, this thesis makes an important contribution to the literature in the following areas. First, I add to our knowledge of temporary agency work by highlighting and explaining how temporary agency workers exhibit individual agency to lessen the effects of precarious work and employment insecurity. Second, many temporary agency workers carry out intense work and this thesis contributes to the literature on temporary agency work by examining how the combined effect of temporality and hard work intensifies their workplace experiences. Third, the relationships experienced by temporary agency workers from within a blended workforce have not been adequately examined from their perspective and this thesis contributes to the literature in this area. Whilst blending suggests a workplace which is smooth and homogenous, I introduce the concept of the mixed-up organisation to appropriately reflect that life on the diverse factory shop floor is far more complicated. Finally, this study reveals how discreet acts of resistance are enacted by temporary agency workers, and in doing so further highlights that these workers possess a surprising degree of individual agency.